Efektivitas Pemberian Kappa-Karaginan Untuk Meningkatkan Resistensi Lobster Air Tawar Cherax quadricarinatus terhadap Infeksi Bakteri Aeromonas hydrophila - Samsidar (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Crayfish Cherax quadricarinatus is one of the fishery commodities that has business prospects not only as an ornamental fish commodity but also as a consumption commodity. Disease attacks caused by bacteria cannot be avoided, so one of the efforts made to increase the resistance of crayfish by giving kappa carrageenan is to increase the resistance of the crayfish. The purpose of this study was to determine the level of resistance of C. quadricarinatus to A. hydrophila bacterial infection by giving kappa carrageenan with different frequencies which is effective for increasing lobster survival after challenge tests with A. hydrophila bacteria. The study was conducted using a completely randomized design (RAL) with five treatments and three replications, namely control (without injection of kappa carrageenan), 1 time, 2 times, 4 times, and 6 times of injection kappa carrageenan. During maintenance, kappa carrageenan was given at a dose of 5 μg/g of oyster by dissolving 2.5 mg in 1 ml of Phosphate Buffer Saline (PBS) and then injected into lobster as much as 20μl/head. on day 30, challenged with A. hydrophila bacteria. The results showed that giving kappa-carrageenan 2, 4, and 6 times showed the same results (P>0.05) on the absolute growth of crayfish. The survival rate of crayfish given kappa-carrageenan showed that the frequency of giving 4 times showed the highest survival rate. Water quality during the study consisting of oxygen 6.25 mg/l, carbodioxide 3.68 mg/l, pH 6.8, ammonia 0.17 mg/l, and temperature 26.9 °C showed that it was still in the range that was feasible as a maintenance media